2014
DOI: 10.22610/jebs.v6i1.464
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Palm Oil Price on the Malaysian Stock Market Performance

Abstract: The performance of a stock market has always become the center of attention for market analysts and investors. Due to its significant role in the economy of a country, the performance of the stock market is always associated with the economic condition of a country. Because of that, this study intends to examine the impact of commodity prices in influencing the behavior of the stock market index specifically by focusing on the palm oil prices. Since Malaysia is one of the major producers of palm oil, the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…Meanwhile [3] employed wavelet correlation in order to investigate the causality between crude palm oil, exchange rate, and KLCI. Their empirical results are in line with [2] except that no causal effects were found between crude palm oil and exchange rate. Additional studies by [4] and [5] expanded their data by incorporating the Islamic stock index namely the FTSE Bursa Malaysia Emas Shariah (BMES).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Meanwhile [3] employed wavelet correlation in order to investigate the causality between crude palm oil, exchange rate, and KLCI. Their empirical results are in line with [2] except that no causal effects were found between crude palm oil and exchange rate. Additional studies by [4] and [5] expanded their data by incorporating the Islamic stock index namely the FTSE Bursa Malaysia Emas Shariah (BMES).…”
Section: Introductionsupporting
confidence: 79%
“…Numerous papers have delved into the repercussions of global commodity price fluctuations on the palm oil industry, yet there remains a dearth of investigations focusing on how these fluctuations affect palm oil companies. A study conducted by [2] emphasised on the impact of palm oil prices on the Kuala Lumpur Composite Index (KLCI) and their findings revealed a cointegration and a positive relationship between these variables. Meanwhile [3] employed wavelet correlation in order to investigate the causality between crude palm oil, exchange rate, and KLCI.…”
Section: Introductionmentioning
confidence: 99%
“…Its plays an important role in the development of any economy's financial system, and it acts as a platform for funding projects and investments capable of creating jobs, reducing poverty, and driving economic growth (Musa & Ibrahim, 2014). Empirical studies confirmed the positive impact of stock market developments on economic growth a country (Nieuwerburgh et al, 2006;Uddin et al, 2013;Masoud, 2013;Nyanaro & Elly, 2017;Nordin & Nordin, 2016).…”
Section: Introductionmentioning
confidence: 81%
“…Hasil penelitiannya adalah dalam jangka panjang adanya hubungan yang negatif di antara IHSG dengan harga minyak sawit. Justru sebaliknya hasil penelitian lain yang dilakukan oleh Nordin, Sabariah;Nordin, Norhafiza;Ismail (2014) di Malaysia menemukan bahwa adanya hubungan positif di antara Kuala Lumpur Composite Index (KLCI) dengan harga CPO dalam jangka pendek ataupun jangka panjang. Dengan demikian, adanya hubungan di antara harga minyak sawit dengan indeks pasar modal.…”
Section: Pendahuluanunclassified